Implementation of School Health Business (SHB) at State Elementary School (ES) Siulak Mukai District, Kerinci District - Septania, Windi; Asparian, Asparian; Ridwan, M.; Guspianto, Guspianto; Sari, Puspita (Rifa'Institute, 2023)
Introduction: School Health Business is a public health business carried out in schools with students and the school community. Objective: The purpose of this SHB program is to improve the quality of education and learning achievement of students who pay attention to healthy behavior and living environment. Method: This study uses qualitative research methods with a descriptive observational approach. Result and Discussion: The results of this study in the aspect of health education Health education was provided from the Public Health Center, but it did not run optimally, because it was not continued continuously and not all schools had the opportunity to attend small doctor training in health education efforts. Conclusion: Health education is not optimal because not all schools can conduct counseling independently and small doctor training is not entirely given to ES in Siulak Mukai District, Health services are not optimal, because facilities and infrastructure are not adequate in some of the schools studied, not all ES in Siulak Mukai District have a healthy school environment.